Reduced Graphene Oxide/Maghemite Nanocomposite for Detection of Lead Ions in Water Using Surface Plasmon Resonance - Ali Abdulkhaleq Abdulhadi Alwahib; Yasmin Mustapha Kamil; Muhammad Hafiz Abu Bakar; Ahmad Shukri Muhammad Noor; Mohd Hanif Yaacob; Hong Ngee Lim; Nay Ming Huang; Mohd Adzir Mahdi (IEEE Photonics Journal)
A prism-based surface plasmon resonance (SPR) sensor deposited with reduced graphene oxide/maghemite is presented for the detection of lead ions (Pb2+) in water. The SPR setup proposed followed the Kretschmann configuration with the installment of the nanocomposite integrated bilayer sensor chip onto the prism. For protection, the nanocomposite active layer was coated with 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimidehydrochloride/N-hydroxysuccinimide. When the sensor was tested with different concentrations of Pb2+ in static water, the limit of detection was achieved at 0.001 ppm with a resonance angle shift of 0.184°. As an improvisation, a sample circulation design was adapted into the setup in order to increase the interaction rate between the sample and the sensing layer. This managed to improve the detection limit to 0.3 ppb.